Шляхи пом’якшення криз при зміні організацією стадій життєвого циклу - Шкрабак, І. В.; Харченко, О. С. (Гельветика, 2024)
У статті обґрунтовано необхідність проактивного підходу до пом’якшення прогнозованих криз, які виникають при переході організації з однієї стадії життєвого циклу на наступну. Різноманіття теоретичних моделей ЖЦО обумовлено різними підходами науковців до визначення стадії, на якій перебуває організація, рушійних сил організаційного розвитку та інших аспектів при загальному розумінні еволюційного характеру життєвого циклу. На прикладі моделі ЖЦО Л. Грейнера розглянуто можливість пом’якшення наслідків організаційних криз, характерних для зміни стадій життєвого циклу організації. Конкретизовані чинники кожної з криз. Пропозиції щодо проактивного управління організаційними трансформаціями представлені відповідно до основних функцій менеджменту. Запропоновані напрями розвитку корпоративної культури як підґрунтя успішного організаційно-структурного редизайну в процесі зміни стадій життєвого циклу організації.

It was analysed the basic models of the organisation's life cycle in the article and justified that, despite differences in the number of stages identified by the authors, approaches to their identification, driving forces of organisation's development and other partial characteristics, the presented models correspond to the general vision of the organisation's evolutionary development and embody three aspects of understanding the essence of the concept of “organisation's life cycle”: as a set of stages and stages of activity; as a period of time; as a sequence of changes. At the same time, organisational changes that occur during the transition from one stage of the life cycle to another are predictable, which allows for proactive management of organisational transformations. Its purpose is to mitigate the next crisis and reduce its negative consequences for the organisation as a socioeconomic system. Based on L. Greiner's model, the specific factors of formation of four organisational crises are specified at each change of one stage of development to another. Proposals to mitigate the predicted crises were developed, which should be implemented at the current stage of development of an organisation as preventive measures that create prerequisites for ensuring the organisational characteristics of the next stage of development without abrupt transitions and imbalance of the socio-economic system. The proposed measures are of a systemic nature but are shown in accordance with the main functions of management: planning, organising, motivating, controlling, which ensures the completeness of organisational change management. The role of corporate culture as a set of generally accepted norms of behavior and interrelationships that determine the format of organisational relations is taken into account, and directions of its transformation are proposed, designed to increase the readiness of staff to provide new organisational characteristics at the next stage of the life cycle. The inexpediency of developing at this stage preventive measures to overcome the crisis that occurs at the end of the stage of growth through cooperation due to the weakness of theoretical and empirical substantiation of the organisational characteristics of the next, sixth stage of the L. Greiner's model of the organisation life cycle and the content of the crisis itself, as well as the failure to take into account the impact of the conditions of the fourth industrial revolution, is substantiated.
Mitigate ways crises when an organisation changes its life cycle stages
Keywords: життєвий цикл організації; криза; чинники; проактивне управління; функції менеджменту; корпоративна культура; organisational life cycle; crisis; factors; proactive management; management functions; corporate culture